2021
DOI: 10.1177/0192513x211044489
|View full text |Cite
|
Sign up to set email alerts
|

Family Communication and Psychological Distress in the Era of COVID-19 Pandemic: Mediating Role of Coping

Abstract: This study aims to examine the association between family communication and psychological distress with coping as a potential mediator. The study also developed and validated the Family Communication Scale (FCS) in the context of COVID-19 pandemic. Participants ( n = 658; 74.9% female) were general public ranged in age between 18 and 58 years (mean age = 26.38, SD = 10.01). The results showed that family communication directly influenced psychological distress and indirectly influenced through approach coping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 54 publications
0
12
0
2
Order By: Relevance
“…According to a study conducted on university students, mental health problems experienced by students in Israel and Russia during the pandemic increased their vulnerability to substance abuse (Yehudai et al, 2020). The COVID-19-related stressors were found to be associated with dysfunctional well-being and mental health outcome such as burnout, psychological distress, loneliness and anxiety Arslan & Kelly, 2022;Çağış & Yıldırım, 2022;Geçer & Yıldırım, 2021;Green et al, 2022aGreen et al, , 2022cKirby et al, 2023;Majercakova Albertova & Bolekova, 2022;Yıldırım, 2021;Yıldırım & Cicek, 2022). A meta-analysis study found that 29.1% of university students had anxiety symptoms (Ebrahim et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study conducted on university students, mental health problems experienced by students in Israel and Russia during the pandemic increased their vulnerability to substance abuse (Yehudai et al, 2020). The COVID-19-related stressors were found to be associated with dysfunctional well-being and mental health outcome such as burnout, psychological distress, loneliness and anxiety Arslan & Kelly, 2022;Çağış & Yıldırım, 2022;Geçer & Yıldırım, 2021;Green et al, 2022aGreen et al, , 2022cKirby et al, 2023;Majercakova Albertova & Bolekova, 2022;Yıldırım, 2021;Yıldırım & Cicek, 2022). A meta-analysis study found that 29.1% of university students had anxiety symptoms (Ebrahim et al, 2022).…”
mentioning
confidence: 99%
“…Based on Cohen's (1988) conventional effect size criterion, it can be concluded that the effect size was small to moderate. The ratio of the number of subjects to items is suggested to be 5:1 with a minimum number of 100 participants (Gorsuch & Hillsdale, 1983) showing that the sample size was sufficient for factor analysis. Using the maximumlikelihood extraction method on Subsample 1, the analysis showed that Bartlett's test for sphericity, [χ2 (45) = 1718.24, p < .001] and Kaiser's measure of sampling adequacy (KMO = .91) were adequate for factor analysis.…”
mentioning
confidence: 99%
“…Stress has been studied in a wide range of fields including psychology, sociology, education, and management (Geçer & Yıldırım, 2021;Moroń et al, 2021;Rehman et al, 2023). Previous research provided evidence that supports the role of stress in alleviating mental and physical health problems (Chandola et al, 2006;Chirico et al, 2022;Hu et al, 2023;Wagner et al, 2000;Yildirim & Alanazi, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…As the global burden of the novel coronavirus disease 2019 (COVID-19) continues to increase, especially in low- and middle-income countries such as Nigeria (provide references), it imposes huge costs on individuals, communities, health systems, and economies across the globe (Arslan and Burke, 2021; Arslan et al, 2021; Otanga et al, 2022; Tanhan et al, 2021; Yıldırım and Solmaz, 2020). COVID-19 pandemic has brought serious psychological impact on healthcare workers, students and the general public globally (Çağış and Yıldırım, 2022; Doyumğaç et al, 2021; Geçer and Yıldırım, 2021; Tanhan, 2020; Tanhan et al, 2020; Tümkaya et al, 2021; Yıldırım and Özaslan, 2021). The pandemic-related restraints, such as spatial distancing, isolation and home quarantine are impacting economic sustainability and wellbeing, which may induce psychological mediators such as sadness, worry, fear, anger, annoyance, frustration, guilt, helplessness, loneliness and nervousness (Bhuiyan et al, 2020; Chirico et al, 2022; Mukhtar, 2020; Yıldırım and Güler, 2022).…”
Section: Introductionmentioning
confidence: 99%